Analisis Faktor-Faktor yang Mempengaruhi Keterlambatan Audit pada Perusahaan Publik di Indonesia - Oktaviani, Shelly; Poniman, Poniman (E-Jurnal Akuntansi; Vol 33 No 3 (2023)DO - 10.24843/EJA.2023.v33.i03.p15, 2023)
The research objective is to understand the effect of Audit Quality, Audit Fee and Company Size on Audit Delay. It is known that the study population totaled 37 food and beverage subsector manufacturing companies which were declared registered on the IDX for the 2017-2021 period. In determining the sample, namely by purposive sampling which then obtained 10 companies. Data collection techniques using documentation techniques. The hypothesis test analysis used is multiple linear analysis. The test results from the t test show Audit Quality with Firm Size whose existence has no effect on audit delay, while audit fees do. This research can provide timely financial information for external parties who need it. Keywords: Quality Audit; Audit Fee; Firm Size; Audit Delay